Assessing Motorcycle Helmet Usage Rates and Road Safety Laws Awareness among Motorcyclists in Bangladesh - Khan, Md. Tanjil Mahmud (International Journal of Applied Sciences and Smart Technologies, 2025)
This research investigates helmet usage rate and motorcyclists’ awareness of road safety laws regarding helmet usage in the Darial Union of Bakerganj Upazila, Bangladesh. A structured questionnaire collected data from 100 participants representing various age groups and professions. Then, data analysis using JASP software revealed significant gaps in helmet usage and awareness of road safety laws regarding helmet usage, particularly among younger individuals aged 15-20 and motorcycle drivers. At the same time, older participants (aged 41 and above) demonstrated higher helmet usage and better understanding; younger riders and those in high-risk professions, such as motorcycle drivers, students, and the unemployed, needed to be more informed and compliant with safety practices. The findings highlight the importance of focused educational efforts and training programs to promote helmet use and raise road safety awareness, particularly in Darial Union's rural districts.